The Role of the Russian Soft Power in Eurasian Integration - M. M. Lebedeva; M. V. Kharkevich (Vestnik MGIMO-Universiteta)
Soft power is analyzed in the article as a resource of integration in the post-soviet area. The author shows that soft power today is an indispensable resource of any integration policy. The amount of soft power defines the depth of integration. Integration in Eurasia is a natural process and eventually it will be of interest for all the states in the region. Soft power will reduce the transaction costs of integration and increase the attractiveness of the project for other states over the long run. A resource of the Russian soft power which will foster the integration processes in the post-soviet region might and ought to be higher education and science. The development of national science may be not only an integration tool, but also a nation idea and a goal for modernization. The author argues that science and higher education will indeed help Russia deepen the Eurasian integration, overcome the lack of trust among its regional neighbors and channel the positive experience of economic integration in adjacent spheres of interstate relations in the post-soviet area.